Better Students Ask More Questions.
Using the method of substitution show that ∫e^(1-x) dx = -e^(1-x) + constant
1 Answer | add yours
Substitute `u = 1-x`
``Then `x = 1 - u ` and `(dx)/(du) = -1`
`int e^((1-x)) dx = int e^u ((dx)/(du)) du = int -e^u du = - int e^u du`
`int e^u du = e^u + "constant"`
so `int e^((1-x)) dx = - int e^u du = -e^u - constant = -e^u + "constant"`
Substituting `x` back in we have that
`int e^((1-x)) dx = - e^((1-x)) + "constant"`
Posted by mathsworkmusic on November 5, 2012 at 3:29 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.